The effectiveness of gynaecology teaching associates in teaching pelvic examination to medical students: a randomised controlled trial. (March 2017) - Janjua, Aisha; Smith, P.; Chu, J.; Raut, N.; Malick, S.; Gallos, I.; Singh, R.; Irani, S.; Gupta, J.K.; Parle, J.; Clark, T.J.
Abstract: Objectives: To assess whether teaching female pelvic examinations using gynaecological teaching associates (GTAs); women who are trained to give instruction and feedback on gynaecological examination technique, improves the competence, confidence and communication skills of medical students compared to conventional teaching. Study design: Randomised controlled trial. Setting: Ten University of Birmingham (UoB) affiliated teaching hospitals in the UK. Population: 492 final year medical students. Methods: GTA teaching of gynaecological examination compared with conventional pelvic manikin based teaching at the start of a five week clinical placement in obstetrics and gynaecology (O&G). Main outcome measures: Student's perception of their confidence was measured on a 10 cm visual analogue scale (VAS). Domains of competence were measured by a senior clinical examiner using a standardised assessment tool which utilised 10 cm VAS and by a GTA using a four point Likert scale. Assessors were blinded to the allocated teaching intervention. Results: 407/492 (83%) students completed both the intervention and outcome assessment. Self-reported confidence was higher in students taught by GTAs compared with those taught on manikins (median score GTA 6.3; vs. conventional 5.8; p = 0.03). Competence was also higher in those taught by GTAs when assessed by an examiner (median global score GTA 7.1 vs. conventional 6.0; p < 0.001) and by a GTA (p < 0.001). Conclusions: GTA teaching of female pelvic examination at the start of undergraduate medical student O&G clinical placements improves their confidence and competence compared with conventional pelvic manikin based teaching. GTAs should be introduced into undergraduate medical curricula to teach pelvic examination.